Outcomes of surgical excison of mass in the eloquent areas of brain : A prospective study at National Academy of Medical Sciences, Bir Hospital - Gautam, Subodh; Bhattarai, Sushil Mohan; Jha, Prabhat; Jha, Binit Kumar; Khadka, Namrata; Paudel, Kumar; Khambu, Bikesh; Shrestha, Rajendra; Bista, Prakash; Jha, Rajiv (Nepal Journal of Neuroscience, 2022)
Introduction: The treatment of choice for high and low-grade gliomas is primarily surgical resection, many gliomas of highly eloquent cortical regions still are not operated because of the impending risk of surgery-related deficits. Tumors of eloquent areas like sensorial, motor and language cortex need to be operated carefully so that the symptoms don’t worsen after surgery. However, Intra operative computerized tomography (IOCT), neuronavigation including optical as well as EM (electromagnetic), Neuromonitoring, stereotaxy and awake surgery increase safety, which allows resection of most of these tumors with a considerably low rate of new deficits postoperatively. Materials and Methods: Between 2021 and 2022, a consecutive series of 30 patients who had undergone surgery for tumors on eloquent area of brain, at National Neurosurgical Referral Center (NNRC), National Academy of Medical Sciences (NAMS), Bir hospital were included in this study. Ethical approval was taken from Institutional review board (IRB) of NAMS for the study. Preoperative functional MRI, DTI scan that revealed mass in eloquent brain areas were evaluated. The preformed proforma was used to collect the data including preoperative karnofsky performance score, age, gender, clinical. Manifestations, size and location of tumor, degree of resection, pathological grade. Patient are followed postoperatively for 3 months and postoperative KPS, morbidity and mortality was recorded. SPSS version 22 was used for statistical analysis. Results: Out of these 30 lesion were 13 (43.3%) were WHO grade IV, 5 (16.6% ) were WHO grade III astrocytoma, 3 (10% ) were WHO grade III oligodendroglioma , 2 (6.6% ) were WHO grade II astrocytoma, 4 ( 13.3%) were WHO grade I astrocytoma, 2 were tuberculoma and 1 was cavernoma. Majority of the patients (70%) (n=21 out of 30) presented with seizures. The mean age of the patient was 41.7 years (ranging from 21-71 years). Male predilection was observed accounting 60 % of the cases. Conclusion: The surgery of eloquent areas of brain though carries the risk of increased post operative neurological deficit, with assistance of advanced technology and experienced surgeons it still feasible option especially for young patients with good karnosky score and low grade tumors which has improved overall survival.